Hubungan Dukungan Keluarga dengan Perilaku Agresi pada Warga Binaan Korban Penyalahgunaan Narkoba di Lapas Kelas II B Muara Sabak - Nando Yoga Pratama; Nurul Hafizah; Marlita Andhika Rahman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Drug abuse remains a serious problem in Indonesia, including in Jambi Province. Its effects are not only physical but also psychological, with aggressive behavior being one of the common consequences. Family support is considered a protective factor that can reduce aggression among inmates with a history of drug abuse. This study aims to describe family support, aggressive behavior, and the relationship between family support and aggressive behavior among inmates who are victims of drug abuse at Class II B Muara Sabak Prison. This research employed a quantitative approach with a correlational design and survey method. The sample was selected using purposive sampling, consisting of drug-related inmates at Class II B Muara Sabak Prison who met the inclusion criteria. The instruments used were the Family Support Scale and the Aggression Behavior Scale. Data were analyzed using correlation tests. The findings revealed a significant negative correlation between family support and aggressive behavior, with a correlation coefficient of r = -0.657. This indicates that higher family support is associated with lower levels of aggressive behavior, both physical and verbal. Family support plays an important role in reducing aggressive behavior among inmates with a history of drug abuse. Correctional rehabilitation programs are recommended to strengthen family involvement in consistently providing support.